PENGARUH FASILITAS BELAJAR DISEKOLAH TERHADAP PRESETASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Buulolo, Yarman (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2024)
Lack of optimal use of learning facilities can hinder student achievement. The aim of this research is to determine the effect of school learning facilities on student learning achievement in economics subjects at Bina Kasih Private High School. The type of research is quantitative research with a descriptive approach. The research results obtained through distributing questionnaires to students stated that school learning facilities influence student learning achievement in economics subjects at Bina Kasih Private High School. Learning facilities make it easier for teachers to explain the material, for example teachers use learning media when teaching, so students quickly understand and understand the subject matter, learning facilities at school have an important role in expediting the learning process by maximizing the use of existing facilities at school, for example using tables and chairs properly. as a place to write, it makes students feel comfortable studying in class, utilizing learning media such as images, audio and so on makes learning less tedious and more interesting, reading books in the library will broaden students' horizons, keeping the room and school environment clean makes the environment beautiful and neat, so that we will be comfortable studying in that environment. Suggestions are: 1) Students should increase their use of learning facilities at school, so that student achievement can increase. The conclusion of this research is that learning facilities at school influence student learning achievement. 2) Teachers should pay more attention to students' abilities in the learning process and maximize the use of learning facilities available at school. 3) It is hoped that the school can maximize the school learning facilities that will be used during the learning process.